A Survey on Different IP Traceback Techniques for finding The Location of Spoofers (International Journal of Engineering and Computer Science, 2015)
The problem of finding  DDoS (Distributed Denial of Service)Attack is one of the  threats in the Internet security field. To get the spoofers, a number of IP traceback mechanisms have been proposed. As their attack root is often hidden The problem  lies in distinguishing the attack traffic from the normal traffic. Different techniques are used to get and identify the origin of DDoS attack with the help of IP Traceback . The most famous techniques in finding the attack source is the IP traceback . Many kinds of traceback techniques are their with each having its own pros and cons. This paper contain and evaluates some of the existing and recently evolving IP traceback techniques with respect to their advantages and disadvantages.